FOREIGN EXCHANGE AND INTERNATIONAL FINANCIAL MARKETS - Yulius Dharma; Maulina Savira; Namira Risqina; Abuzar Alqifahri Mahdi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The currency used as the basis for recording transactions and reporting financial information for companies in Indonesia is the rupiah. financial transactions stated in foreign currencies (other than rupiah) must first be translated into rupiah in accordance with PSAK no. 10. Foreign currency refers to the currency of each country used in international trade. every United States dollar (USD), euro (EUR), British pound (GBP), Japanese yen (JPY) and so on. the international market is a place where foreign exchange is traded, the international financial market operates in a decentralized manner and takes place electronically through a computer network.